2015
DOI: 10.5194/isprsarchives-xl-1-w4-159-2015
|View full text |Cite
|
Sign up to set email alerts
|

Local Algorithm for Monitoring Total Suspended Sediments in Micro-Watersheds Usin Drones and Remote Sensing Applications. Case Study: Teusacá River, La Calera, Colombia

Abstract: ABSTRACT:An empirical relationship of Total Suspended Sediments (TSS) concentrations and reflectance values obtained with Drones' aerial photos and processed using remote sensing tools was set up as the main objective of this research. A local mathematic algorithm for the micro-watershed of the Teusacá River at La Calera, Colombia, was developed based on the computing of four component of bands from consumed-grade cameras obtaining from each their corresponding reflectance values from procedures for correcting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Thus, the generated TSS maps for Lake Unisinos are shown in Figure 6. Although several studies show good results using regression methods to predict TSS [2,7,11,[15][16][17][18][19], others, such as Song et al [6], Amanollahi et al [10], Moridnejad et al [12], and Wu et al [25], compared the two methodologies (RA and ANN) and obtained results indicating better quality in the prediction of the data through an ANN, signaling the capacity of the neural networks to model more complex and non-linear relations between the parameters. Only Kong et al [8] reported that an ANN did not present better results than regression methods for TSS predictions in their area of study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the generated TSS maps for Lake Unisinos are shown in Figure 6. Although several studies show good results using regression methods to predict TSS [2,7,11,[15][16][17][18][19], others, such as Song et al [6], Amanollahi et al [10], Moridnejad et al [12], and Wu et al [25], compared the two methodologies (RA and ANN) and obtained results indicating better quality in the prediction of the data through an ANN, signaling the capacity of the neural networks to model more complex and non-linear relations between the parameters. Only Kong et al [8] reported that an ANN did not present better results than regression methods for TSS predictions in their area of study.…”
Section: Resultsmentioning
confidence: 99%
“…Although some applications of UAVs for water quality parameters monitoring, such as chlorophyll-a [1,[15][16][17], organic matter [18], and suspended solids [1,[18][19][20], have been demonstrated in the literature, there are still few studies focused on this application. For suspended solids monitoring, for example, Veronez et al [18] and Saénz et al [19] used regression analyses between TSS values measured in the laboratory and the UAV responses in the visible and near infrared (NIR) regions to generate their prediction models.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of conventional cameras and narrow-band imaging sensors (for example, Micasense Altum with RBG, Red Edge, NIR, and Thermal IR bands; Headwall Hyperspec sensors) have been adapted to drones and aircraft, enabling measurements across the solar reflective spectrum, as well as emissive thermal infrared. The following studies have used drones for a variety of water quality measurements: primary production and trophic state [ 88 ], harmful algal blooms [ 89 , 90 ], macrophytes [ 91 , 92 ], chlorophyll-a [ 93 ], total suspended matter (TSM) [ 94 ], and turbidity [ 95 ]. It is safe to assume that emerging technologies will provide more capabilities in monitoring water quality parameters.…”
Section: Overview Of Observational Methods and Platformsmentioning
confidence: 99%